Dynamic anti-plane analysis for interfacial cracks emanating from an eccentric circular cavity in piezoelectric bi-materials. Issue 6 (2nd November 2021) - An, Ni; Song, Tian-shu; Hou, Gangling; Yang, Bo; Pan, Haizhu
ABSTRACT: Since piezoelectric materials are mainly used as sensitive components, various defects such as cracks, cavities, and inclusions have a critical influence on the application of materials. Based on the study of the dynamic anti-plane characteristics for radial crack emanating from a circular cavity in piezoelectric bi-materials, this paper aims to establish the mechanical model of interfacial cracks emanating from an eccentric circular cavity. Green function method, coordinate transformation method, conjunction and crack-deviation techniques are adopted to solve Fredholm's equations, expressing the dynamic stress intensity factor (DSIF) theoretically. As cases, numerical results of DSIFs are plotted and discussed with different geometric and physical parameters by Fortran program. Eccentric defects exist more widely in materials and have higher difficulty in solving, compared with non-eccentric ones. Numerical results show that the dynamic stress intensity factor at the crack tip of the eccentric model is greater than that of the non-eccentric model, which indicates that the eccentricity of the cavity is more likely to cause crack growth and damage to piezoelectric materials. Therefore, it is of great theoretical and engineering significance to study the fracture behavior of materials based on eccentric defects.